2017
DOI: 10.2147/idr.s145844
|View full text |Cite
|
Sign up to set email alerts
|

Detection of hepatitis C virus (HCV) among health care providers in an Egyptian university hospital: different diagnostic modalities

Abstract: BackgroundHepatitis C virus (HCV) infection has received much attention and is placed at the core of the infection control agenda. It is considered as a major public health problem in Egypt, where the highest prevalence of HCV exists. The great risk of exposure to infection of health care providers (HCPs) has highlighted the urgent need for implementing an infection control program.ObjectiveThe purpose of this study was to detect the prevalence of HCV infection among HCPs in Zagazig University Hospitals and to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…This observation is in contrast to other studies conducted in developing countries, which reported high of non-adherence rates. (24,30,31) it is worth noting that measuring adherence in our study was based on what the participated HCWs answered, not what was actually observed.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This observation is in contrast to other studies conducted in developing countries, which reported high of non-adherence rates. (24,30,31) it is worth noting that measuring adherence in our study was based on what the participated HCWs answered, not what was actually observed.…”
Section: Discussionmentioning
confidence: 96%
“…(24) There are considerable gaps in terms of standard infection control practices and application of infection control policies during health care delivery in Egypt. (31) HCWs should have an accurate policy for the notification of their occupational risks.…”
Section: Discussionmentioning
confidence: 99%
“…All CLD cohort diagnosis was performed by PCR testing for hepatitis C virus infection and hepatitis B virus infection [106,107] clinically validated for positive chronic infection for more than 6 months. Secondly, all subjects were tested by diagnostic ultrasonography (U/S) examination to exclude cirrhosis.…”
Section: Participants and Collection Of Clinical Samplesmentioning
confidence: 99%
“…In this patient population, cirrhosis may progress within 20 years of infection. With hepatic decompensation and hepatocellular carcinoma, these longstanding consequences have put more hindrances on resources in an already overstressed Egyptian healthcare system [8] . The four is the most public genotype of HCV in the Middle East and Africa, mostly Egypt…”
Section: Introductionmentioning
confidence: 99%